The role of immunohistochemistry P53 ,Ki-67, Bcl-2 In colorectal carcinoma prognosis - أحمد عيسى; داود علي; صالح رينا (Latakia University Journal -Medical Sciences Series, 2021)
BACKGROUND: The incidence of colorectal cancer is rising over time, as it is the most common cause of cancer deaths after lung cancer. And the survival rate of 5 years is weak. METHODS: We investigated the following IHC status p53, Ki-67, Bcl-2 in 80 colorectal cancer cases distributed over the years 2017-2019 from Tishreen University Hospital reviewers. The relationship of IHC prevalence to prognostic factors: age, tumor size, stage, grade, histological pattern, and presence of distant or lymph metastases. The cross-sectional statistical study was completed by using the SPSS program. RESULTS: the tumor size in half of the cases >5 cm, 60% of the tumors were on the left side, metastases appeared in the lymph nodes in 53.75% of the cases, 10% of the patients suffered from distant metastases upon diagnosis, the results of IHC staining are as follows p53 (positive 48.75%), Bcl-2 (positive 55%) and severe positive Ki-67, 26.25%. CONCLUSION: The presence of strong positivity Ki-67, P53 indicates an increase in aggressive biological behavior, which calls for effective aggressive treatment with these tumors to improve the prognosis.Bcl2 high expression correlated with good prognosis in CRC